Effects of Teriparatide and Alendronate on Functional Recovery from Spinal Cord Injury and Postinjury Bone Loss - Shuai Wang; Jingliang Zhu; Yuping Feng; Yuchen Hua; Gangjun You; Jahui Su; Benchao Shi (Biomedicines)
Objectives: This study evaluated the efficacy of teriparatide (TPTD) and alendronate (ALN) in mitigating bone loss, enhancing bone structure, and facilitating motor function recovery following spinal cord injury (SCI). Methods: All the rats were allocated into four groups: a sham surgery group (SHAM group), a normal saline group (SCI + NS group), a TPTD treatment group after SCI (SCI + TPTD group), and an ALN treatment group after SCI (SCI + ALN group). The Basso, Beattie, and Bresnahan (BBB) scores and gait analyses were used to assess the motor abilities of rats following SCI and the effects of treatment. HE staining, Masson’s trichrome staining, and LFB staining were performed to evaluate the extent of spinal cord tissue damage. Micro-CT was used to measure 12 bone-related parameters of the proximal tibia and create 3D images, and structural changes in the proximal tibial bone tissue were observed under a light microscope after HE staining. Results: After 12 weeks of treatment, the micro-CT data indicated that TPTD significantly increased key bone indicators, such as bone mineral density, after SCI (p < 0.01), whereas ALN did not significantly improve these indicators (p > 0.05). Compared with the SCI + NS group, the SCI + TPTD group presented significantly greater BBB scores and near-normal gait parameters (p < 0.05). Analyses of pathological sections revealed that TPTD significantly reduced the cavity area in the spinal cord after SCI, decreased the proportion of scar tissue, and increased the retention of neural myelin (p < 0.05). However, ALN had no significant effect on these indicators (p > 0.05). Conclusions: TPTD was more effective than ALN at mitigating bone loss and promoting motor function recovery after SCI, and it demonstrated significant advantages in reducing spinal cord damage and improving tissue structure.